The Role Of Context In Lexical Semantics: Analyzing How Different Contexts Affect The Meanings Of Words And Phrases, With Examples From Various Languages - Xolmatova, Hilola; Sharafutdinov, Nodirxon (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2025)
The study of lexical semantics, a subfield of linguistics that looks at word meanings and how context affects interpretation, is examined in this article. To illustrate how words carry meaning and change depending on linguistic, cultural, and situational settings, it offers a thorough examination of several important theoretical frameworks, including componential analysis, prototype theory, frame semantics, and distributional semantics. Cross-linguistic research between Uzbek and English reveals both language-specific and universal patterns in semantic interpretation, especially with regard to politeness tactics, idiomatic phrases, and polysemy. With an emphasis on the need of semantic shifts for language acquisition, natural language processing (NLP), and intercultural communication, the challenges in contextual analysis and machine translation are also covered in the study; a comparative approach is adopted, so contributing to a more comprehensive knowledge of how meaning is constructed, interpreted, and changed across languages and contexts.